The Effectiveness of Integrating Grammar and Writing Instructions through Systemic Functional Linguistics (Tamaddun, 2025)
This study examines the effectiveness of integrating grammar instruction with writing activities through the framework of Systemic Functional Linguistics (SFL) to enhance the writing skills of senior high school students in an English as a Foreign Language (EFL) context. The research employed a pre-experimental one-group pre-test and post-test design involving 29 students from Class XI.TL.1 at SMAN 11 Makassar. Over five instructional sessions, students were taught grammar in a contextualized manner by embedding it within the writing of hortatory exposition texts, guided by SFL principles such as Theme–Rheme organization, transitivity, and cohesive devices. Data were collected through writing tasks administered before and after the intervention and analyzed using descriptive statistics, paired-sample t-tests, and normalized gain (N-Gain) analysis to determine the magnitude and significance of improvement. The findings revealed a statistically significant increase in students’ grammar accuracy, coherence, and cohesion in writing, with an N-Gain score indicating upper-medium effectiveness. These results demonstrate that integrating grammar and writing instruction through SFL not only bridges the gap between form and function but also supports the development of meaningful, well-structured texts. The study underscores the pedagogical value of adopting functional grammar approaches in EFL classrooms and recommends further research to explore their application across different genres and proficiency levels.